Molecular Identification of Yersinia enterocolitica Isolated from Different Sources in Erbil City: Molecular Identification of Yersinia enterocolitica - Faruq Yousif, Omer; Sorchee, Sawsan M. (Cellular and Molecular Biology, 2022)
Yersinia enterocolitica ranks third among the pathogens that often cause the digestive disorder. It is transmitted to humans through food materials, especially contaminated meats. This research aimed to survey the frequency of Yersinia enterocolitica in sheep local products, especially meat, in Erbil. To carry out this study, 500 samples of raw milk, soft cheese, ice cream, and meat were collected by random sampling from different shops in Erbil City of Iraq. The samples were divided into four groups, including raw milk, soft cheese, ice cream, and meat. Many microbiological tests (culture, & staining, biochemical Tests, Vitek 2, and species-specific Polymerase Chain Reaction (PCR) amplicon for 16S RNA gene) were performed. Results showed that 5.1% of all of the studied samples were contaminated with Yersinia enterocolitica. Analysis of the results showed that meat is more contaminated than other samples. Also, the sequenced DNA evolutionary phylogeny tree of Yersinia enterocolitica isolates showed that all bacteria originated from the same genus and species. Therefore, it is recommended to pay special attention to this issue in order to avoid health and economic risks.